Study of the phytochemical diversity of segregated Rhus coriaria pericarp and seeds oil and their antifungal and antibacterial activity - Dotsha Jaleel Raheem; Sabah Rahman , Hero; Qadr FaqeAbdulla , Nareen; Ahmed Ahmed , Akhter (Zanco Journal of Pure and Applied Sciences, 2025)
Sumac fruits are used in food and as a remedy, but their seeds are often discarded as waste despite making up a large proportion of the fruit’s weight. This research therefore examines the chemical composition and biological activities of oils from sumac pericarp and seeds in an attempt to find potential uses for the seeds in comparison to the long-used pericarp. Both oils were found to contain alkanes and fatty acids. The pericarp oil also contained caryophyllenes. Fatty acid methyl ester analysis revealed oleic, linoleic, palmitic, and stearic acids as major components in both parts. Pericarp oil contained more saturated fatty acids, while seed oil showed higher content of unsaturated fatty acids. The pericarp oil also contained greater amounts of total phenols, β-carotene and exhibited higher radical scavenging activity. Elemental analysis found K, P, Si, Cl, S, and Ca as major elements in both pericarp and seeds oil. Both oils showed moderate inhibition against Candida albicans. The pericarp oil strongly inhibited Escherichia coli and seed oil inhibited Acinetobacter baumannii. Moderate activity was observed against Klebsiella pneumoniae, Pseudomonas aeruginosa, and Staphylococcus aureus by both pericarp and seeds oil. The findings suggest both oils have potential as nutritional and antimicrobial agents.